Affordable Incident Response Using Cloud-Based Open-Source Data Pipelines with Integrated Threat Intelligence Platforms - Vijay Kartik Sikha (International Journal of Intelligent Systems and Applications in Engineering, 2019)
The incident response landscape has undergone significant transformations in recent years, driven by the escalating complexity and sophistication of cyber threats. This paper explores the evolution of incident response from static relational databases to dynamic, cloud-based solutions and NoSQL databases, and examines the role of threat intelligence platforms, machine learning, and automation in enhancing the speed and accuracy of incident response efforts. The paper also discusses the benefits and limitations of cloud-based and open-source solutions and highlights the importance of integrating various technologies and systems to create a comprehensive incident response strategy. The future of incident response is characterized by increased automation, integration, and innovation, and organizations must prioritize incident response and invest in the technologies and strategies that will enable them to detect, respond to, and mitigate cyber threats effectively.